Review article predictors and outcomes of dengue-associated acute kidney injury - Ajib Diptyanusa (2022)
Dengue viral infections present with a wide clinical spectrum ranging from asymptomatic to severe manifestations with organ involvement. The term “expanded dengue syndrome” has been commonly used to illustrate the unusual or atypical manifestations; acute kidney injury (AKI) is one of the atypical manifestations of this syndrome. The use of heterogeneous criteria to determine the presence of AKI in dengue patients due to the vast diversity in populations led to difficulties in assessing the true incidence of dengue-associated AKI. This review presents a variable, but often high, frequency of dengue-associated AKI among vastly diverse populations with various disease severities. Dengue-associated AKI is not an uncommon complication, and its importance has often been neglected during the management of dengue patients. The risk factors and certain clinical and laboratory findings commonly reported among dengue patients with AKI should be considered to support a timely diagnosis and case management. This review highlights the need for clinicians to be aware of dengue-associated AKI to reduce the morbidity and mortality associated with this common and important tropical disease.